Temperature, Workplace Safety, and Labor Market Inequality - R. Jisung Park; Nora Pankratz; A. Patrick Behrer (Institute of Labor Economics (IZA), 2021)
Using data covering the universe of injury claims from the nation's largest worker's compensation system (2001-2018), we explore the relationship between temperature and workplace safety and its implications for labor market inequality. Hotter temperature increases workplace injuries significantly, causing approximately 20,000 injuries per year. The effects persist in both outdoor and indoor settings (e.g. manufacturing, warehousing), and for injury types ostensibly unrelated to temperature (e.g. falling from heights), consistent with cognitive or cost-related channels. The risks are substantially larger for men versus women; for younger versus older workers; and for workers at the lower end of the income distribution, suggesting that accounting for workplace heat exposure may exacerbate total compensation inequality. We document a decline in the heat-sensitivity of injuries over the study period, suggesting significant scope for adaptation using existing technologies.
Keywords: J20; J32; I18; Q50; 330; inequality; labor; workplace safety; temperature; climate change; adaptation